Risk factors for patent ductus arteriosus in preterm neonates - Novia Bernati; Ria Nova; Julniar M. Tasli; Theodorus Theodorus (Paediatrica Indonesiana, 2014)
Background The reported prevalences of patent ductus arteriosus(PDA) in preterm neonates vaty, and are currently unknown inPalembang. Birth weight, ges tational age, asphyxia, histoty ofantenatal steroid use, hyaline membrane disease (HMD), raceand ethnicity, are potential risk factors for PDA.Objective To determine the prevalence of PDA and its riskfactors in preterm neonates at Mohammad Hoesin Hospital,Palembang.Methods This cross-sectional study was conducted from October2011 to April 2012. Echocardiographic examinations wereperformed on 242 preterm neonates aged 15 hours to 7 days. Datawas taken from medical records and interviews, and analyzed byChi square and logistic regression analyses.Results Patent ductus arteriosus was found in 142 (58.7%)preterm neonates with a prevalence ratio of 1.43. Neonates withbirthweight ::;;2,000 grams tended to have 1.9 (95% CI 1.17 to3.32) rimes higher risk for PDA (P=0.01). Neonates ::;;JO weeksgestation were also at 1.9 rimes higher risk for PDA (P=0.16).Probabilities for PDA occurrence in neonates with asphyxia,without antenatal corticosteroids and HMD were 1.6 (95%CI 1.13 to 3.36) rimes, 1.3 (95%CI 0.73 to 2.50) times and 2.2(95%CI 1.29 to 3.72) rimes higher risk for PDA, respectively(P=0.22, 0.41, and 0.005, respectively).Conclusion Birth weight and HMD are statistically significantrisk factors of PDA, but the more significant one is HMD.